Analisis Hukum Sanksi Pidana Kerja Sosial (Community Service Order) dalam Perspektif Hukum Islam - M. Hasbi Ash-shiddiqqi; Alhusni Alhusni; Yudi Armansyah (Institut Agama Islam Negeri Kerinci, 2021)
Discourse on renewal of the draft law on the criminal code (RUU-KUHP) has long been discussed. One of the newest aspects studied is about criminal social work or community service orders. This idea was born because prison sentences in Indonesia have not had a positive impact on convicts. Not to mention the issue of over-capacity of prisons that caused prison chaos until the operational costs of the prison were enormous. This juridical-normative study concludes that: The social work criminal design is in accordance with the criminal law punishments. Even so far in the Criminal Code it has been known as punishment through supervision mechanisms or fines. That is, beyond the criminal sanction, there are alternatives to punishment that can be given. In contrast, in Islamic law, in fact, it is in line with the principle of criminal sanctions for social work. Where, Islam tends to avoid prison sentences. Because prisons with various patterns are more likely to have a detrimental effect on convicts than on the mashlahat side.